An Analysis of Assertive Illocutionary Acts Found in President Joe Biden's State Speech - Basilia Anita Setiawati; Komang Dian Puspita Candra (Institut Agama Islam Negeri Palopo, 2024)
This study aims to delineate the categories of assertive illocutionary acts that are present in the state speech of President Joe Biden. Searle's (1979) classification of illocutionary acts was implemented by the researcher in this study. The data analyzed in this research is qualitative descriptive, as the results may be presented in the form of sentences or words. President Joe Biden's 2024 State of the Union Address and assertive illocutionary acts serve as the focus of this study. From the data sources of this research, the researcher was able to identify five distinct classifications of assertive illocutionary acts. This research found 51 data of assertive illocutionary acts in President Joe Biden’s state speech. In addition, the most dominant classification of assertives that was found in the data source is informing with 20 (39,21%) occurrences followed by stating with 14 (27,45%) occurrences, asserting with 11 (21,56%), boasting with 4 (7,84%). The least dominant types of assertive illocutionary act that was found namely; complaining with 2 (3,92%) occurrences. The Informing type is said to be the most dominant because speakers provide information to their listeners more often than conveying ordinary things. Additionally, the speaker's meaning has been interpreted in accordance with the circumstances in which the utterance was delivered. Additional advantages of this research include the enhancement of listeners' confidence and enthusiasm for the speaker.